The Influence of Employee Loyalty and Work Environment on Employee Work Productivity at CV. Umega Bahtera Sanjaya - Rayhan Demas Hafiyyan; Azis Azis; Rd. Herman Sofyandi (PT Mattawang Mediatama Solution, 2023)
Business in Indonesia is currently experiencing rapid growth with the increasing number of new companies, making business competition in Indonesia increasingly high for business practitioners. One of the competitions is in the procurement of goods and services, which requires human resources that are able to compete and survive in the competition within a company's industrial activities. Carrying out business activities cannot be separated from the human resource management to complete the work and achieve the company's/organization's goals. This research is titled